2015
DOI: 10.4236/pp.2015.610049
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Solubility Enhancement of Mirtazapine: Effect of Cosolvent and Surfactant

Abstract: The poor aqueous solubility of drugs is a challenging problem faced by pharmaceutical scientists in drug formulation. Cosolvency and micellization techniques have been severally used to enhance the solubility of poorly aqueous soluble drugs. Mirtazapine, a tetracyclic antidepressant used for the treatment of moderate to severe depression and anxiety, has very poor aqueous solubility. The objective of the study was to investigate the effect of solubilizing agents (cosolvents and surfactants) on the aqueous solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…There were no significant differences in the solubility of PR in various pH condition and ethanol concentrations between 48 and 72 h, displayed no noticeable differences, which indicated that the solubility of PR had reached equilibrium. The low water solubility of PR may be due to the inability of water, to break into the lattice structure of PR [19]. On the other hand, when the co-solvent systems were used, the PR solubility increased when the ethanol concentration increased.…”
Section: Discussionmentioning
confidence: 99%
“…There were no significant differences in the solubility of PR in various pH condition and ethanol concentrations between 48 and 72 h, displayed no noticeable differences, which indicated that the solubility of PR had reached equilibrium. The low water solubility of PR may be due to the inability of water, to break into the lattice structure of PR [19]. On the other hand, when the co-solvent systems were used, the PR solubility increased when the ethanol concentration increased.…”
Section: Discussionmentioning
confidence: 99%
“…The samples were agitated for 48 hours at 37 ± 1 °C in an incubator shaker. The solution was passed through a 0.45 μm Millipore filter, and the drug concentration was evaluated by UV- Vis spectrophotometer at λ max 293 nm (K. E. Ezealisiji et al., 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, it has a low bioavailability of about 50%. It was estimated that increasing its water solubility might result in increased bioavailability and reduce the dose required to achieve the desired therapeutic effect (K. E. Ezealisiji et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…This indicates a high hydrophobicity, but it does dissolve in ethanol and an acidic condition. The MTZ has a low bioavailability (50%), high protein-binding (85%), and a long half-life (20-40 h) [4]. MTZ has a relatively narrow therapeutic index and should be individually optimized to obtain a therapeutic effect [5].…”
Section: Introductionmentioning
confidence: 99%